O Moderno no progresso de uma cultura urbana, escolar e religiosa e a Educação Secundária do Instituto Presbiteriano Gammon (1892-1942) - Pereira, Jardel Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper is a historiographical analysis of a confessional private school institution. Presbyterian missionaries from the United States founded, in 1869, the International School in the city of Campinas, SP, which was transferred to Lavras, MG, in 1892 and received the name of Evangelical Institute. Through this study we sought to understand how this school was constituted throughout time, building a differentiated and remarkable scholar culture for its time. A key factor to its development was its urban insertion, at a time when many other institutions were already present in the land of Lavras and had the support of local authorities. With time, the mission of contributing to the progress, not only of the city, but also of Brazil, was incorporated into their educational ideals, creating a school system that included students from various Brazilian locations. The modern category was the object of understanding the progress of the urban, school and religious culture present both in Secondary Education and in other schools belonging to the Evangelical Institute in an attempt to understand how the latter and other institutions called themselves and were also entitled. A web of relationships was established by its founders, Samuel Rhea Gammon and Carlota Kemper, who were dedicated to evangelization and direction of the Institute. From these networks of sociability, both conquered the trust of lavrenses and were inserted in the history of the city they helped educate

Neste trabalho, faz-se uma análise históriográfica de uma instituição escolar confessional privada. Missionários presbiterianos, vindos dos Estados Unidos da América, iniciaram, na cidade de Campinas-SP, em 1869, o Colégio Internacional, que foi transferido para Lavras-MG em 1892, onde recebeu o nome de Instituto Evangélico. Com esta pesquisa pretendeu-se compreender como essa escola foi se constituindo ao longo do tempo, construindo uma cultura escolar diferenciada e marcante para sua época. Um fato determinante para seu desenvolvimento foi sua inserção urbana num momento em que outras tantas instituições já se faziam presentes em terras lavrenses, tendo o apoio de autoridades locais. Com o tempo, foi incorporada aos seus ideais educacionais a missão de contribuir para o progresso não somente da cidade, mas também do Brasil, criando um sistema educacional que abrangeu alunos de vários locais brasileiros. A categoria moderno foi objeto de compreensão do progresso da cultura urbana, escolar e religiosa presente tanto na educação secundária como nas outras escolas pertencentes ao Instituto Evangélico, na tentativa de compreender como ela e as outras instituições se autointitulavam assim e eram também intituladas, como fator importante para o desenvolvimento urbano, cultural e religioso. Uma teia de relações foi estabelecida por seus fundadores, Samuel Rhea Gammon e Carlota Kemper, que se dedicaram à evangelização e à direção do Instituto. No estabelecimento de redes de sociabilidade, ambos conquistaram a confiança dos lavrenses e foram inseridos na história da cidade que ajudaram a instruir
Keywords: Educação - Historia; Escolas - História; Antropologia educacional; Ensino religioso; Escola Religião; Education